Comprehensive microbiota analysis and UV-C intervention in embalmed cadavers: A retrospective study on anatomical teaching and preservation. - Das, Arghya; Banerjee, Manotosh; Ray, Subhenjit; Mandal, Lopamudra; (Ghosh), Reena Ray; Roy, Sanchita (Student's Journal of Health Research Africa, 2024)
Background Post-mortem specimens used for anatomy teaching are commonly embalmed using chemical compositions to maintain tissue quality and avoid putrefaction. This study was conducted during a dissection course on embalmed dissected cadavers, involving the cultivation of samples before and after exposure to UV-C radiation to elucidate microbiota growth. This study aimed to provide scientific insights into formalin embalming, guiding future research on mitigating microbiota growth through interventions like ultraviolet-C radiation and other modifications. Materials and methods This retrospective study was conducted at the Department of Anatomy and Microbiology, Diamond Harbour Government Medical College and Hospital, West Bengal, India. 96 samples were collected at each step of the study. Results Samples were collected from six sites of two embalmed cadavers along with a cadaver transferring trolley, Mackintosh gown used for dissections & cadaver tank fluid and processed for bacteriological and mycological culture. A total number of incubations were done in 96 samples, for the growth of anaerobic, aerobic & mycological species before & after UV-C radiation on the cadaver. After UV-C exposure for one and a half hours, mycological growth was reported from only three sites of cadavers, but no bacteriological growth was found in any of the samples. Conclusion It has been concluded from the study that there were viable bacteria and fungi found on multiple sites and surfaces of embalmed cadavers & dissection hall materials, which impose significant health hazards to healthcare professionals & medical students. Recommendations This study recommends integrating routine UV-C radiation treatment into disinfection protocols for embalmed cadavers and dissection materials to reduce microbiota growth. Additionally, it suggests further research on the efficacy of non-toxic chemical disinfectants as a potential intervention to enhance safety in anatomical education environments.